PENERAPAN MODEL PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDS MUHAMMADIYAH 002 ALAM PANJANG KECAMATAN RUMBIO JAYA - Asmar Asmar; Hendri Marhadi; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This Research is background by lowering nya assess to learn the mathematics of student of class of IV of Elementary School of Private sector Muhammadiyah (SDSM) 002 Alampanjang with the average value 62,73 staying in category is not complete. Target doing of this research is to improve the result learn the mathematics of student of class of IV SDSM 002 Alampanjang with the applying PMRI of at items develop;build the space (cube and log). This research represent the research of tidakan class consisted of by two cycle. this Subjek Research [is] student of class of IV SDSM 002 Alampanjang of teaching year 2015/2016 with the student amount as much 22 one who is consisted of by 12 student people and 10 student people. Pursuant to analysis of observation sheet in the reality activity learn and student activity from cycle I until cycle II also experience of the make-up of. Activity result learn at cycle of I meeting of first until siklu II meeting of second for example: 53,57%, 64,29%, 75%, 82,14% with each category enough, good, goodness and good. While result of observation of student activity of at cycle of I meeting of first up to cycle of II meeting of second is: 53,57%, 60,71%, 71,43%, 78,57% each with the category enough, enough, good, good. Result learn the student of before applying PMRI own the nialai mean 62,73 (is not complete). After applied by approach PMRI at cycle of I of average value of student mount to become 64,77 (is not complete). While at cycle of II average value daily restating of II also experience of the improvement become 73,18 (complete). Percentage of[is make-up of result learn the student from elementary score to cycle I of equal to 2,04% and percentage of[is make-up of result learn from elementary score to cycle II become equal to 8,41%. Pursuant to inferential mentioned that applying model the PMRI can improve the result learn the mathematics of student of class of IV SDSM 002 AlampanjangKeyword: The Model of Study PMRI, Result of Learning Mathematics .